Mapping thermoelectric properties of polycrystalline n-type Bi2Te3-xSex alloys by composition and doping level - Jung, Sung-Jin; Lee, Byeong-Hyeon; Won, Sung Ok; Kim, Seong Keun; Park, Hyung-Ho; Kim, Jin-Sang; Baek, Seung-Hyub (Elsevier BV, 2020)
The thermoelectric figure-of-merit (zT) is a general standard used to evaluate the performance of thermoelectric materials. However, the performance of thermoelectric devices is largely affected by other properties such as electrical conductivity, thermal conductivity, and the power factor, depending on applications and boundary conditions. Therefore, it is beneficial to have a comprehensive map where the full range of thermoelectric properties are presented to design a high performance thermoelectric module optimized for any customized applications. In this study, we explore the thermoelectric properties of the n-type (1-x)Bi2Te3-xBi2Se3 alloys from x = 0.04 to x = 0.20 with various SbI3 doping levels. We used a hot extrusion technique to obtain a textured microstructure of our specimens to take advantage of their strong anisotropic nature. The SbI3 donor dopant enabled the precise control of electron density in the range of similar to 10(19) cm(-3). Using this process, we constructed a thermoelectric property map as a function of the composition of the bismuth tellurium selenides and doping levels, to provide guidance on designing high performance thermoelectric modules for various applications. (C) 2020 Elsevier B.V. All rights reserved.